FAKTOR-FAKTOR ANAK DITERLANTARKAN DAN DAMPAKNYA (STUDI DI KOTA AMBON) - Rahakbauw, Nancy (Istek Widuri Jakarta, 2016)
This paper aims to describe the factors that lead to neglect of children, as well as the impact experienced by children who are neglected. This study used a qualitative approach and descriptive analysis. Subjects were children who had been neglected by the age category 10 to 18 years old and their parents or family.From the analysis of the research findings, it was shown that the triggers that lead to neglected children is a parental divorce and mistreatment received by children, as well as family economics and low parental education. The impact of divorce and abuse experienced by children led to the rights and needs of children are not even fulfilled properly and optimally. This situation eventually encourage children to do activities outside the home to become hawkers, washerman grave, domestic workers and motorcycle taxi drivers. By carrying out an activity or activities outside the home that takes time and effort, they do not have time to go to school.